UNIVERSITIES UNDER THE MAGNIFYING GLASS OF GLOBAL UNIVERSITY RANKINGS: THE PERFORMANCE OF ENTREPRENEURSHIP EDUCATION - Carolina LLORENTE-PORTILLO; Laura GÓMEZ-URQUIJO; Marta ENCISO SANTOCILDES (Challenges of the Knowledge Society)
The EU and public entities have shown a keen interest in promoting Entrepreneurship Education in universities through policy initiatives and regulations. This study aims to examine the extent to which Entrepreneurship is incorporated into the ranking methodologies of Higher Education Institutions (Universities). Consequently, the research question posed is: How do the indicators employed by global rankings capture the performance of universities in Entrepreneurship Education? Utilizing data from the International Ranking Expert Group Observatory, this study selects Global University Rankings categories, which encompass a total of 30 rankings as the sample. Our findings reveal that while the European Commission strive to create a public framework that supports entrepreneurship education, the sampled international rankings do not consider entrepreneurship as a criterion to evaluate university performance.